A Strategic Budgeting Model and Development Strategy for Private Universities: A Study of the Toraja Indonesian Christian University - Oktavianus Pasoloran; Ade Lisa Matasik (Return : Study of Management, Economic and Bussines, 2026)
This research aims to develop an integrated strategic budgeting model for Private Universities (PTS) with a case study at the Indonesian Christian University of Toraja. Although UKI Toraja has implemented a digital financial system and activity-based budgeting (ABB), the relationship between budget allocation and strategic objectives has not been fully identified as required in performance-based budgeting (PBB). This study uses a qualitative approach through document analysis, in-depth interviews, and observation of the budgeting process to examine the characteristics of the current budgeting system and the internal-external factors that affect it. The results show that UKI Toraja has a good financial system foundation, but still needs to strengthen performance indicators, consolidate cross-unit planning, and results-based evaluation mechanisms. These findings are the basis for formulating an integrated strategic budgeting model that synergizes ABB, UN principles, and institutional development directions. The novelty of the research lies in the thorough integration between the budgeting system and the institutional strategy designed according to the context of Indonesian private universities. The resulting model is expected to be a reference for private universities in increasing the effectiveness of resource allocation and achieving strategic goals.